THE USE OF DIGITAL MEDIA IN DEVELOPING STUDENTS’ ENGLISH ACADEMIC WRITING SKILLS - Bobomurodova Iroda Abduvaxobovna (Journal of new century innovations, 2022)
Annotation: This article mainly discusses the importance of English language instruction in the classroom while teaching academic writing. Moreover, the role of digital resources in developing students’ academic writing skills and methods for implementing in teaching it as well.